Characterization of effluent organic matter from different coking wastewater treatment plants. (July 2018) - Yang, Wenlan; Wang, Jicheng; Hua, Ming; Zhang, Yanyang; Shi, Xinxing
Abstract: Effluent organic matter (EfOM) in bio-treated wastewater generally has negative impacts on advanced wastewater treatment processes. Thus, a comprehensive characterization of EfOM would help determine feasibility of wastewater treatment. The aim of this work was to characterize EfOM originating from four coking wastewater treatment plants (WTPs) in China, using specific UV absorbance (SUVA), EfOM fractionation, size exclusion chromatography, and excitation-emission matrix (EEM) fluorescence spectroscopy. It was found that the predominant species in all the EfOM samples were hydrophobic compounds with high SUVA values. The molecular weight (MW) distribution of the sampled EfOM was in the range of 300–1500 Da, and stronger UV absorbance was observed in the high MW (＞ 500 Da) region. The EEM fluorescence spectra showed that aromatic compounds accounted for a large proportion of the sampled EfOM based on the fluorescence regional integration technique. The abovementioned analysis highlights the similarities in the characteristics of the EfOM originating from different coking WTPs, regardless of treatment plant design. Meanwhile, significant differences between the characteristics of the EfOM in coking wastewater and municipal wastewater were observed. Graphical abstract: Highlights: Effluents from four coking WTPs of typical design were sampled to characterize EfOM. Predominant species in all samples were hydrophobic compounds with high SUVA values. Molecular weights of the sampled EfOM were mainly in the range 500–1500 Da. Aromatic compounds accounted for a large proportion of the sampled EfOM.